Formulation of Roselle Flower Extract Gel (Hibiscus sabdariffa L) as a Disclosing Solution - Nurilawaty, Vitri; Priharti, Dwi; Sukmawati, Ai Emalia; Sasongko, Bimo Gigih; Tulandi, Silvester Maximus; Purnama, Tedi (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Plaque is a soft deposit attached to the teeth consisting of various types of microorganisms from saliva and food waste. Plaque cannot be seen because it is transparent, like the color of translucent white glass. The way to see plaque is to use a contrast material such as a dye (red/purple) in the form of a liquid or gel called a disclosing solution. It is usually found in gel and liquid form. But in use in humans there are many shortcomings because they are expensive, quite expensive and often contain harmful chemicals. One of the herbal plants that can be used as an alternative material as a disclosing solution is Rosella (Hibiscus sabdariffa L.) which can be used for its properties in the field of Prevention of Dental and Oral Diseases and has antibacterial and remineralizing effects. Methods: This research is an experimental study on the development of Rosella Flower Extract (Hibiscus sabdariffa L.) in the form of a gel in disclosing solution. The research was carried out from June to August 2021 at the Pharmacognosy Laboratory, Department of Pharmacy and Food Analysis, Health Polytechnic of Jakarta II and Dental Health Laboratory, Health Polytechnic of Jakarta I. Disclosing solution prepared from dried Rosella Flowers (Hibiscus sabdariffa L.) was obtained as much as 1000 grams. from the Research Institute for Spices and Medicinal Plants, Bogor. Hedonic testing was carried out on 34 students of the Department of Dental Health, Health Polytechnic of Jakarta I. Results: The disclosing solution preparation in the form of a gel from rosella flower extract had good organoleptic test results. The expected red color corresponding to the color of the disclosing solution is at a concentration of 70%. The average pH of the disclosing solution in the form of a gel was 4.95. The average dispersion of the gel preparation is 5.7. 5. The average adhesion of gel preparations at all concentrations is 1.44 seconds. The hedonic test was obtained that most of the respondents had a neutral opinion on all disclosing gel preparations. Conclusion: The preparation of Roselle Flower Extract Gel (Hibiscus sabdariffa L) can be used as an alternative disclosing solution